Late-Pregnancy Dysglycemia After Negative Testing for Gestational Diabetes and Risk of the Large-for-Gestational-Age Newborns: A Nest Case-Control Study Based on the Xi'an Longitudinal Mother-Child Cohort Study - He, Zhangya; Mi, Yang; Yang, Hexiang; Ji, Jing; Gao, Jiayi; Zhang, Wanyu; Wu, Pei; Xu, Zhangrui; Wang, Shanshan; Luo, Xiaoqin (Frontiers in Pediatrics, 2022)
Background The implications of gestational diabetes mellitus (GDM) on the short- and long-term health outcomes of both mother and child have been extensively studied. However, studies related to negative Oral Glucose Tolerance Test (OGTT) results in the second trimester but dysglycemia in late pregnancy on maternal and infant pregnancy outcomes are rare. Methods We conducted a nest case-control study within the Xi'an Longitudinal Mother-Child Cohort study (XAMC) to investigate the risk of adverse pregnancy outcomes in mothers and children with maternal negative mid-pregnancy OGTT results but high glycated hemoglobin (HbA1c) levels (≥5.7%) in late pregnancy. All target women who delivered from January 1st, 2017 to December 31st, 2018 in Northwest Women's and Children's Hospital in Xi'an were enrolled as the case group (HbA1c ≥ 5.7%). Others with HbA1c < 5.7% but without GDM were selected as the control group (HbA1c < 5.7%) by matching with the same delivery period. The logistic regression models were used to find out the risk factors of adverse pregnancy outcomes in the target population. Results A total of 2,116 and 1,907 women were finally enrolled in the case and control groups, respectively. Compared to the control group, more newborns with macrosomia (9.2% vs 4.1%, P < 0.001) and large for gestational age (LGA) (23.7% vs. 13.5%, P < 0.001), but less small for gestational age (SGA) (4.4% vs. 6.1%, P = 0.017) were found in the case group. The differences in other outcomes were not statistically significant. The multiple logistic regression analysis showed that gestational age, fetal length, prenatal HbA1c, and total cholesterol (TG) were independent risk factors for newborns with large-for-gestational-age (LGA). The case group had a 2.516-fold (95% CI, 1.692–3.739) risk of delivering LGA newborns compared to the control group. Conclusion The glycemic management during the late pregnancy of non-GDM women should be given special consideration to reduce the risk of overweight offspring at birth.